Magnetic microcrystalline glass brazing filler metal, preparation method thereof and ferrite connecting method
By using a magnetic microcrystalline glass solder composed of Bi2O3, B2O3, NiO and Fe2O3 of a specific ratio and sonicating during the welding process, the problems of magnetic performance attenuation and high connection temperature of ferrite joints in the prior art are solved, and ferrite is efficiently connected at a lower temperature, improving the strength of the welded joint and the distribution uniformity of the magnetic phase.
Patent Information
- Application Number
- CN202510021949.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, there is magnetic performance attenuation at the joints of microwave ferrite devices, and when welding with magnetic microcrystalline glass brazing, the connection temperature is high, the number of precipitation of magnetic phases is small, and the distribution uniformity is poor.
A magnetic microcrystalline glass solder is provided, and its components include Bi2O3, B2O3, NiO and Fe2O3. The bismuth boron glass matrix is constructed through a specific ratio, and the precipitation of the magnetic phase is promoted by sonication during the welding process. The magnetic microcrystalline glass solder has a low connection temperature, can achieve ferrite connection from 600°C to 700°C, and improve the strength of the welded joint and the distribution uniformity of the magnetic phase.
The ferrite connection at lower temperatures (600°C to 700°C) is achieved, which improves the strength of the welded joint and the distribution uniformity of the magnetic phase, thereby improving the magnetic performance of the joint.
Smart Images

Figure CN119797765A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of welding materials, and in particular to a magnetic microcrystalline glass solder and a preparation method thereof, and a ferrite connection method. Background Art
[0002] Yttrium iron garnet ferrite (YIG ferrite) is a magnetic material widely used in microwave devices. At present, microwave ferrite devices are often connected by gluing. Since the colloid itself is not magnetic, the joints of microwave ferrite devices often have magnetic performance attenuation. Glass brazing refers to a welding method that uses glass solder as a brazing material and can achieve the construction of a specific functional joint by adjusting the composition of the glass solder. Glass solders are mainly divided into three categories: amorphous glass solders, composite glass solders and microcrystalline glass solders. Among them, microcrystalline glass solders can introduce the target precipitation phase into the joint through crystallization, and introduce the performance of the target precipitation phase into the joint while retaining the original excellent performance of the glass matrix. The magnetic phase generated by magnetic microcrystalline glass solder after heat treatment can introduce magnetism, making it a better choice for connecting ferrites. However, the softening temperature of magnetic glass is very high, requiring a higher connection temperature. In addition, the number of magnetic phases precipitated in the welded joint obtained by welding with magnetic microcrystalline glass solder is small and the distribution uniformity is poor, which has a great impact on the performance of the joint. Summary of the invention
[0003] The problem solved by the present invention is at least one of the following problems: how to obtain a magnetic microcrystalline glass solder with a lower connection temperature, so as to realize the connection of ferrites at a lower temperature. When using the magnetic microcrystalline glass solder for ferrite connection, how to increase the precipitation amount and distribution uniformity of the magnetic phase in the welded joint.
[0004] To solve the above problems, the present invention provides a magnetic microcrystalline glass solder, which comprises, by mole, 30 to 50 parts of Bi2O3, 30 to 40 parts of B2O3, 5 to 20 parts of NiO, and 5 to 20 parts of Fe2O3.
[0005] Compared with the related art, the magnetic microcrystalline glass solder provided by the present invention is composed of Bi2O3, B2O3, NiO and Fe2O3 in a specific ratio, wherein Bi2O3 and B2O3 are used to construct a bismuth boron glass matrix so that the magnetic microcrystalline glass solder can be in a glassy state, and NiO and Fe2O3 are used to ensure that a magnetic phase (such as Ni2FeO4) is precipitated in the magnetic microcrystalline glass solder during the welding process. It has been found through experiments that the magnetic microcrystalline glass solder has a lower connection temperature, and the connection of ferrites can be achieved at 600°C to 700°C using the magnetic microcrystalline glass solder, and the welded joint strength of the obtained ferrite connector is relatively high.
[0006] The present invention also provides a method for preparing the magnetic microcrystalline glass solder as described above, comprising:
[0007] Step S1, after Bi2O3, B2O3, NiO and Fe2O3 are uniformly mixed, heating treatment is performed to obtain molten glass liquid;
[0008] Step S2, annealing the molten glass liquid, cooling it in the furnace, and obtaining a magnetic microcrystalline glass solder.
[0009] Optionally, in step S1, the heating treatment is performed at a temperature of 1000° C. to 1050° C. and for a time of 25 min to 35 min.
[0010] Optionally, in step S2, the annealing treatment is performed at a temperature of 300° C. to 400° C. and for a time of 1.5 h to 2.5 h.
[0011] The present invention also provides a ferrite connection method, comprising:
[0012] Step M1, making the magnetic glass-ceramics solder as described above into a solder sheet;
[0013] Step M2, placing the solder sheet between two ferrite base materials to be soldered to form a sandwich structure of components to be connected;
[0014] Step M3, heating the components to be connected to 450°C to 550°C at a first heating rate, performing a first insulation treatment, and then heating to 600°C to 700°C at a second heating rate, performing a second insulation treatment, to obtain a ferrite connector; wherein, during the first insulation treatment, the components to be connected are continuously subjected to ultrasonic treatment.
[0015] Compared with the related art, the ferrite connection method provided by the present invention can promote the precipitation of the magnetic phase by heating the components to be connected to 450°C to 550°C for heat preservation, and ultrasonically treat the components to be connected during the precipitation of the magnetic phase, which can make the magnetic phase more evenly distributed in the welded joint, and is conducive to improving the performance of the welded joint. In addition, the method provided by the present invention can achieve the connection of ferrites at a relatively low temperature (600°C to 700°C).
[0016] Optionally, in step M3, the ultrasonic wave used in the ultrasonic treatment has a frequency of 15 kHz to 25 kHz, an amplitude of 10 μm to 100 μm, and a power of 100 W to 3000 W.
[0017] Optionally, in step M3, the first heat preservation treatment lasts for 1 min to 3 min.
[0018] Optionally, in step M3, the second heat preservation treatment lasts for 15 minutes to 60 minutes.
[0019] Optionally, in step M3, the first heating rate is 5°C / min to 10°C / min.
[0020] Optionally, in step M3, the second heating rate is 5°C / min to 10°C / min. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is an XRD image of the welded joint of the ferrite connector prepared in Example 1;
[0022] Figure 2 is a scanning electron microscope image of the welded joint of the ferrite connector prepared in Example 1;
[0023] Figure 3 It is a scanning electron microscope picture of the welding joint of the ferrite connector prepared in the comparative example. DETAILED DESCRIPTION
[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. Although certain embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be interpreted as being limited to the embodiments described herein. On the contrary, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the drawings and embodiments of the present invention are only for exemplary purposes and are not intended to limit the scope of protection of the present invention.
[0025] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0026] The term "including" and its variations used in this article are open inclusions, that is, "including but not limited to"; the term "based on" is "based at least in part on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one other embodiment"; the term "some embodiments" means "at least some embodiments"; the term "optionally" means "optional embodiments". The relevant definitions of other terms will be given in the following description. It should be noted that the concepts of "first" and "second" mentioned in the present invention are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship. In addition, the terms "first" and "second" are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, the meaning of "multiple" is two or more.
[0027] A magnetic microcrystalline glass solder provided in an embodiment of the present invention comprises, in terms of molar parts, 30 to 50 parts of Bi2O3, 30 to 40 parts of B2O3, 5 to 20 parts of NiO, and 5 to 20 parts of Fe2O3.
[0028] The magnetic microcrystalline glass solder provided in the embodiment of the present invention is composed of Bi2O3, B2O3, NiO and Fe2O3 in a specific ratio, wherein Bi2O3 and B2O3 are used to construct a bismuth boron glass matrix so that the magnetic microcrystalline glass solder can be in a glassy state, and NiO and Fe2O3 are used to ensure that a magnetic phase (such as Ni2FeO4) is precipitated in the magnetic microcrystalline glass solder during the welding process. It has been found through experiments that the magnetic microcrystalline glass solder has a relatively low connection temperature. The connection of ferrites can be achieved at 600°C to 700°C using the magnetic microcrystalline glass solder, and the welded joint strength of the obtained ferrite connector is relatively high.
[0029] The embodiment of the present invention further provides a method for preparing the magnetic glass-ceramics solder as described above, comprising:
[0030] Step S1, after Bi2O3, B2O3, NiO and Fe2O3 are uniformly mixed, heating treatment is performed to obtain molten glass liquid;
[0031] Step S2, annealing the molten glass liquid, cooling it in the furnace, and obtaining a magnetic microcrystalline glass solder.
[0032] In some embodiments of the present invention, in step S1, the temperature of the heating treatment is 1000° C. to 1050° C., and the time is 25 min to 35 min.
[0033] In some embodiments of the present invention, in step S2, the annealing treatment is performed at a temperature of 300° C. to 400° C. and for a time of 1.5 h to 2.5 h.
[0034] An embodiment of the present invention further provides a ferrite connection method, comprising:
[0035] Step M1, making the magnetic glass-ceramics solder as described above into a solder sheet;
[0036] Step M2, placing the solder sheet between two ferrite base materials to be soldered to form a sandwich structure of components to be connected;
[0037] Step M3, heating the components to be connected to 450°C to 550°C at a first heating rate, performing a first insulation treatment, and then heating to 600°C to 700°C at a second heating rate, performing a second insulation treatment, to obtain a ferrite connector; wherein, during the first insulation treatment, the components to be connected are continuously subjected to ultrasonic treatment.
[0038] The ferrite connection method provided by the embodiment of the present invention can promote the precipitation of the magnetic phase by heating the components to be connected to 450°C to 550°C for heat preservation, and ultrasonically treat the components to be connected during the precipitation of the magnetic phase, so as to make the magnetic phase more evenly distributed in the welded joint, which is beneficial to the improvement of the performance of the welded joint. In addition, the method provided by the embodiment of the present invention can realize the connection of ferrite at a relatively low temperature (600°C to 700°C).
[0039] In some embodiments of the present invention, in step M3, the ultrasonic wave used in the ultrasonic treatment has a frequency of 15 kHz to 25 kHz, an amplitude of 10 μm to 100 μm, and a power of 100 W to 3000 W.
[0040] In some embodiments of the present invention, in step M3, the first heat preservation treatment lasts for 1 min to 3 min.
[0041] In some embodiments of the present invention, in step M3, the second heat preservation treatment is performed for 15 to 60 minutes.
[0042] In some embodiments of the present invention, in step M3, the first heating rate is 5° C. / min to 10° C. / min.
[0043] In some embodiments of the present invention, in step M3, the second heating rate is 5° C. / min to 10° C. / min.
[0044] The present invention is further described below in conjunction with specific embodiments.
[0045] Example 1
[0046] A1. Mix four kinds of powders of Bi2O3, B2O3, NiO and Fe2O3 in a molar ratio of 40:35:12.5:12.5, and then heat-treat them to obtain molten glass; wherein the temperature of the heating treatment is 1000°C and the time is 30 minutes.
[0047] A2. Annealing the molten glass liquid and cooling it in the furnace to obtain a magnetic microcrystalline glass solder; wherein the annealing temperature is 350° C. and the time is 2 hours.
[0048] A3. The magnetic glass-ceramic solder is made into a solder sheet; the thickness of the solder sheet is 0.4 mm.
[0049] A4. Place the solder sheet between two ferrite base materials to be soldered to form a sandwich structure of a component to be connected; wherein the thickness of the ferrite base materials to be soldered is 2 mm.
[0050] A5. Heat the components to be connected to 450°C at 10°C / min, perform the first heat preservation treatment, and then heat to 600°C at 10°C / min, perform the second heat preservation treatment, to obtain a ferrite connector; wherein, the first heat preservation treatment time is 3 minutes, the second heat preservation treatment time is 60 minutes, and during the first heat preservation treatment, the components to be connected are continuously subjected to ultrasonic treatment, and the frequency of the ultrasonic wave used in the ultrasonic treatment is 20kHz, the amplitude is 50μm, and the power is 1500W.
[0051] Example 2
[0052] The difference from Example 1 is that step A1 is: after uniformly mixing four powders of Bi2O3, B2O3, NiO and Fe2O3 in a molar ratio of 50:40:20:20, heat treatment is performed to obtain molten glass liquid; wherein the heating treatment temperature is 1000°C and the time is 30 minutes.
[0053] Example 3
[0054] The difference from Example 1 is that step A5 is: heating the components to be connected to 550°C at 10°C / min, performing the first insulation treatment, and then heating to 700°C at 10°C / min, performing the second insulation treatment, to obtain a ferrite connector; wherein the first insulation treatment time is 1 min, and the second insulation treatment time is 15 min. During the first insulation treatment, the components to be connected are continuously ultrasonically treated, and the frequency of the ultrasonic wave used in the ultrasonic treatment is 25 kHz, the amplitude is 50 μm, and the power is 3000 W.
[0055] Example 4
[0056] The difference from Example 1 is that step A5 is: heating the components to be connected to 500°C at 10°C / min, performing the first insulation treatment, and then heating to 650°C at 10°C / min, performing the second insulation treatment, to obtain a ferrite connector; wherein the first insulation treatment time is 2 minutes, the second insulation treatment time is 35 minutes, and during the first insulation treatment, the components to be connected are continuously ultrasonically treated, and the frequency of the ultrasonic wave used in the ultrasonic treatment is 15kHz, the amplitude is 10μm, and the power is 1000W.
[0057] Comparative Example
[0058] The difference from Example 1 is that step A5 is: heating the components to be connected to 450°C at 10°C / min, performing the first insulation treatment, and then heating to 600°C at 10°C / min, performing the second insulation treatment to obtain a ferrite connector; wherein the first insulation treatment time is 3 minutes, and the second insulation treatment time is 60 minutes.
[0059] Experimental example
[0060] The welded joint of the ferrite connector prepared in Example 1 was tested by XRD, and the results are shown in Figure 1 ,from Figure 1 It can be seen that the welded joint of the ferrite connector prepared in Example 1 contains the magnetic phase Ni2FeO4. The welded joints of the ferrite connectors prepared in Example 1 and the comparative example were analyzed by scanning electron microscope. The results are shown in FIG. Figure 2 and Figure 3 ,from Figure 2 and Figure 3 It can be seen that, compared with the comparative example, the amount of magnetic phase precipitated in the welded joint in Example 1 is larger and the distribution is more uniform. The shear strength of the welded joints of the ferrite connectors prepared in Examples 1 to 3 and the comparative example was tested, and the results are shown in Table 1. It can be seen from Table 1 that, compared with the comparative example, the shear strength of the welded joints of the ferrite connectors prepared in Examples 1 to 3 is higher.
[0061] It should be noted that Figure 1 In the figure, the curve above "Glass-YIG interface" is the XRD curve of the sample at the interface between the weld and the ferrite base material of the ferrite connector prepared in Example 1, and the curve below "inside the weld" is the XRD curve of the sample in the middle part of the welded joint of the ferrite connector prepared in Example 1. Figure 2 and Figure 3 In the figure, some magnetic phases are framed by boxes as an example. Figure 2 and Figure 3 The materials with similar color and appearance to the boxed magnetic phase are also magnetic phases.
[0062] Table 1
[0063] serial number Shear strength(MPa) Example 1 92 Example 2 95 Example 3 94 Comparative Example 85
[0064] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A magnetic glass-ceramic solder, characterized in that: In terms of molar parts, its components include: Bi2O3: 30 to 50 parts, B2O3: 30 to 40 parts, NiO: 5 to 20 parts, and Fe2O3: 5 to 20 parts.
2. The method for preparing the magnetic microcrystalline glass solder according to claim 1, characterized in that: include: Step S1, after Bi2O3, B2O3, NiO and Fe2O3 are uniformly mixed, heating treatment is performed to obtain molten glass liquid; Step S2, annealing the molten glass liquid, cooling it in the furnace, and obtaining a magnetic microcrystalline glass solder.
3. The method for preparing the magnetic microcrystalline glass solder according to claim 2, characterized in that: In the step S1, the temperature of the heating treatment is 1000° C. to 1050° C., and the time is 25 min to 35 min.
4. The method for preparing the magnetic microcrystalline glass solder according to claim 2, characterized in that: In the step S2, the annealing treatment is performed at a temperature of 300° C. to 400° C. and for a time of 1.5 h to 2.5 h.
5. A method for connecting ferrites, characterized in that: include: Step M1, preparing a solder sheet from the magnetic glass-ceramics solder as claimed in claim 1; Step M2, placing the solder sheet between two ferrite base materials to be soldered to form a sandwich structure of components to be connected; Step M3, heating the components to be connected to 450°C to 550°C at a first heating rate, performing a first insulation treatment, and then heating to 600°C to 700°C at a second heating rate, performing a second insulation treatment, to obtain a ferrite connector; wherein, during the first insulation treatment, the components to be connected are continuously subjected to ultrasonic treatment.
6. The ferrite connection method according to claim 5, characterized in that: In the step M3, the ultrasonic wave used in the ultrasonic treatment has a frequency of 15 kHz to 25 kHz, an amplitude of 10 μm to 100 μm, and a power of 100 W to 3000 W.
7. The ferrite connection method according to claim 5, characterized in that: In step M3, the first heat preservation treatment lasts for 1 minute to 3 minutes.
8. The ferrite connection method according to claim 5, characterized in that: In the step M3, the second heat preservation treatment lasts for 15 minutes to 60 minutes.
9. The ferrite connection method according to claim 5, characterized in that: In the step M3, the first heating rate is 5°C / min to 10°C / min.
10. The ferrite connection method according to claim 5, characterized in that: In the step M3, the second heating rate is 5°C / min to 10°C / min.